Energy storage element

JP7631754B2Active Publication Date: 2025-02-19GS YUASA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020194745
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-24
Publication Date
2025-02-19
Estimated Expiration
2040-11-24

AI Technical Summary

Benefits of technology

【0008】 本発明の一側面によれば、放電状態において電極体の少なくとも一部が押圧されている蓄電素子であって、充放電サイクル後の抵抗増加率が低減された蓄電素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631754000002
    Figure 0007631754000002
  • Figure 0007631754000003
    Figure 0007631754000003
  • Figure 0007631754000004
    Figure 0007631754000004
Patent Text Reader

Abstract

To provide a power storage element reduced in resistance increase rate after charge / discharge cycles, the power storage element having an electrode body at least part of which is pressed in a discharge state.SOLUTION: A power storage element 1 includes an electrode body 2 having a negative electrode including a negative electrode active material, and an electrolyte. At least part of the electrode body is pressed in a discharge state, and the negative electrode active material contains solid natural graphite.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an energy storage element. [Background technology]

[0002] Due to their high energy density, non-aqueous electrolyte secondary batteries, typified by lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. In addition, as electricity storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors, electricity storage elements using electrolytes other than non-aqueous electrolytes, etc. are also widely used.

[0003] A typical energy storage element includes an electrode assembly in which a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material are stacked with a separator interposed therebetween. Such an electrode assembly is housed in a container together with an electrolyte to form an energy storage element. Carbon materials such as graphite are widely used as negative electrode active materials (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-222933 A [Patent Document 2] JP 2017-069039 A Summary of the Invention [Problem to be solved by the invention]

[0005] According to the inventors' investigations, an energy storage element designed so that at least a part of the electrode body is in a compressed state in a discharged state tends to have an improved capacity retention rate after charge-discharge cycles. However, an energy storage element designed in this way has the disadvantage of having a high resistance increase rate after charge-discharge cycles.

[0006] An object of the present invention is to provide an energy storage element in which at least a portion of an electrode assembly is pressed in a discharged state, and in which the rate of increase in resistance after charge / discharge cycles is reduced. [Means for solving the problem]

[0007] An energy storage element according to one aspect of the present invention comprises an electrode body having a negative electrode containing a negative electrode active material, and an electrolyte, wherein at least a portion of the electrode body is pressed in a discharged state, and the negative electrode active material contains solid natural graphite. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide an energy storage element in which at least a part of an electrode body is pressed in a discharged state, and in which the rate of increase in resistance after charge / discharge cycles is reduced. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a perspective view showing an embodiment of an energy storage element. [Diagram 2] FIG. 2 is a schematic diagram showing an embodiment of an electricity storage device configured by assembling a plurality of electricity storage elements. [Diagram 3] FIG. 3 is a graph showing the capacity maintenance rates of the energy storage elements of Reference Examples 2 to 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the energy storage element disclosed in this specification will be described.

[0011] An energy storage element according to one aspect of the present invention comprises an electrode body having a negative electrode containing a negative electrode active material, and an electrolyte, wherein at least a portion of the electrode body is pressed in a discharged state, and the negative electrode active material contains solid natural graphite.

[0012] The electric storage element according to one aspect of the present invention is an electric storage element in which at least a part of the electrode body is pressed in a discharged state, and the resistance increase rate after a charge / discharge cycle is reduced. The reason for this is unclear, but the following reason is presumed. In general, in an electric storage element, when the active material expands due to the inflow and outflow of ions accompanying charge and discharge, a part of the electrolyte impregnated in the electrode body decreases the pore volume of the electrode body and flows out of the electrode body. Then, when the active material contracts, the electrolyte flows into the electrode body. At this time, if the electrolyte does not return completely to the electrode body, a part of the electrode body where the electrolyte is depleted occurs, and the reaction area of ​​the electrode that contributes to charge and discharge in the electrode body decreases, causing an increase in resistance. Here, when the electrode body is in a pressed state, the gap between the active materials tends to narrow when the active materials expand, so the amount of electrolyte that flows out of the electrode body increases. Then, when the active material contracts, the electrolyte is less likely to return to the inside of the electrode body in the pressed state, so the above-mentioned increase in resistance becomes significant. In addition, when the electrolyte is exhausted in the electrode body, the reaction area of ​​the electrode that contributes to charging and discharging in the electrode body is reduced, and the current density of charging and discharging is increased. Therefore, if charging and discharging are repeated without the electrolyte being completely returned to the electrode body, the current density increases, and the decomposition of the electrolyte is promoted, and the storage element is deteriorated, causing an increase in resistance. In contrast, in the storage element according to one aspect of the present invention, solid natural graphite, which has a small volume change during charging and discharging, is used as the negative electrode active material, so that even though at least a part of the electrode body is pressed, the amount of electrolyte that flows out of the electrode body when the active material expands is reduced, and the amount of electrolyte that does not return to the electrode body when the active material contracts is reduced. Therefore, it is presumed that the storage element according to one aspect of the present invention makes it difficult for the electrolyte to be exhausted in the electrode body, and reduces the rate of increase in resistance after charging and discharging cycles. In addition, since the energy storage element according to one aspect of the present invention is configured so that at least a portion of the electrode body is pressed in a discharged state, the capacity retention rate after charge / discharge cycles tends to be high. Although the reason for this is unclear, it is speculated that the electrode body is less likely to be wrinkled due to at least a portion of the electrode body being pressed, the distance between the electrodes (between the positive electrode and the negative electrode) is made uniform, and local deterioration of the active material is suppressed, resulting in an increase in the capacity retention rate.

[0013] Here, the "discharged state" of the energy storage element refers to the state after the following operations have been performed. First, the energy storage element is charged at a constant current of 1C until it reaches the charge end voltage during normal use, and then it is charged at a constant voltage, and the total charging time is 3 hours, resulting in a fully charged state. After a 10-minute break, it is discharged at a constant current of 1C until it reaches the lower limit voltage during normal use. This state is called the discharged state. Here, normal use refers to the case where the energy storage element is used by adopting the charging and discharging conditions recommended or specified for the energy storage element, and, if a charger for the energy storage element is provided, the charger is used to use the energy storage element.

[0014] The term "solid" in solid natural graphite means that the interior of a particle of natural graphite is filled and substantially no voids exist. More specifically, "solid" means that in a cross section of a particle observed in an SEM image obtained using a scanning electron microscope (SEM), the area ratio of voids within the particle to the area of ​​the entire particle (void ratio) is 2% or less. In a preferred embodiment, the area ratio of the voids in solid natural graphite may be 1% or less. The "area ratio of voids within a particle to the area of ​​the entire particle (porosity)" of a graphite particle can be determined by the following procedure. (1) Preparation of the measurement sample The negative electrode to be measured is fixed with thermosetting resin. A cross-section polisher is used to expose the cross section of the negative electrode fixed with resin, and a measurement sample is prepared. The negative electrode to be measured is prepared according to the following procedure. The storage element is discharged at a constant current of 0.1C to the lower limit voltage for normal use, and placed in a discharged state. The storage element in this discharged state is disassembled, the negative electrode is removed, and it is thoroughly washed with dimethyl carbonate, and then dried under reduced pressure at room temperature. The work from disassembling the storage element to obtaining the SEM image is carried out in a dry air atmosphere with a dew point of -40°C or less. (2) Acquiring SEM images To obtain SEM images, a JSM-7001F (manufactured by JEOL Ltd.) scanning electron microscope is used. SEM images are obtained by observing secondary electron images. The acceleration voltage is 15 kV. The observation magnification is set so that 3 to 15 graphite particles appear in one field of view. The obtained SEM image is saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus are appropriately set so that the contours of the graphite particles are clearly visible. (3) Cutting out the outline of the graphite particles The image cutting function of the image editing software Adobe Photoshop Elements 11 is used to cut out the outlines of the graphite particles from the acquired SEM image. This cutting out of the outlines is performed by using the quick selection tool to select the area outside the outlines of the graphite particles, and then editing everything except the graphite particles to a black background. If the outlines of less than three graphite particles could be cut out at this time, another SEM image is acquired and the process is repeated until the outlines of three or more graphite particles can be cut out. (4) Binarization The image of the first graphite particle among the cut-out graphite particles is binarized using the image analysis software PopImaging 6.00, with a threshold value set to a concentration 20% lower than the concentration at which the intensity is at its maximum. The area of ​​the higher concentration side is calculated through the binarization process, and this is taken as the "area S1 of the voids within the particle." Next, the image of the first graphite particle, the same as before, is subjected to a binarization process with a threshold density of 10. Through the binarization process, the outer periphery of the graphite particle is determined, and the area inside the outer periphery is calculated to obtain the "area S0 of the entire particle." Using the calculated S1 and S0, the ratio of S1 to S0 (S1 / S0) is calculated to calculate the "area ratio R1 of the voids within the particle to the area of ​​the entire particle" for the first graphite particle. The above binarization process is also performed on the images of the second and subsequent graphite particles among the cut-out graphite particles, and the areas S1 and S0 are calculated. Based on the calculated areas S1 and S0, the area ratios R2, R3, ... of the voids in each graphite particle are calculated. (5) Determination of void area ratio The "area ratio of voids within a particle to the entire area of ​​the particle (porosity)" is determined by calculating the average value of all void area ratios R1, R2, R3, ... calculated by the binarization process.

[0015] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. The "discharged state" of the carbon material refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic lithium (Li) as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the oxidation-reduction potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing the carbon material relative to the oxidation-reduction potential of Li. In other words, an open circuit voltage of 0.7 V or more in the single-electrode battery means that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material.

[0016] It is preferable that the negative electrode active material is substantially made of the solid natural graphite. In such a case, the volume change of the negative electrode active material during charging and discharging is smaller, so that the resistance increase rate after charging and discharging cycles tends to be further reduced. Note that "the negative electrode active material is substantially made of solid natural graphite" means that the content of solid natural graphite in the entire negative electrode active material is 99 mass% or more.

[0017] It is preferable that the negative electrode further contains sodium carboxymethylcellulose (CMC-Na). In this case, the resistance increase rate after charge-discharge cycles tends to be further reduced. The reason for this is unclear, but it is thought that CMC-Na increases the dispersibility of each component (for example, the dispersibility of binder particles on the surface of the negative electrode active material).

[0018] Hereinafter, the energy storage element according to one embodiment of the present invention, the configuration of the energy storage device, the manufacturing method of the energy storage element, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0019] <Electricity storage element> The electric storage element according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, an electrolytic solution, and a container for accommodating the electrode assembly and the electrolytic solution. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The electrolytic solution is present in a state in which the positive electrode, the negative electrode, and the separator are impregnated. As an example of an electric storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery") will be described.

[0020] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0021] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H4160 (2006).

[0022] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased while increasing the energy density per volume of the secondary battery. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate.

[0023] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0024] The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.

[0025] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ)O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.

[0026] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0027] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.

[0028] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0029] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0030] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0031] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0032] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the active material can be stably held.

[0033] Examples of thickeners include polysaccharide polymers such as carboxymethylcellulose (CMC) and methylcellulose. CMC is usually used in the form of a metal salt such as a sodium salt, an ammonium salt, etc. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.

[0034] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0035] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0036] The positive electrode can be produced, for example, by applying a positive electrode mixture paste directly or via an intermediate layer to a positive electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The positive electrode mixture paste contains each component constituting the positive electrode active material layer, including a positive electrode active material and optional components such as a conductive agent and a binder. The positive electrode mixture paste usually further contains a dispersion medium.

[0037] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0038] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0039] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.

[0040] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0041] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0042] The negative electrode active material contains solid natural graphite. The negative electrode active material of the secondary battery contains solid natural graphite, so that the resistance increase rate after charge / discharge cycles is reduced. The natural graphite may have four peaks at a diffraction angle 2θ in the range of 40 to 50° in an X-ray diffraction pattern using CuKα radiation measured before charge / discharge or in a discharged state. These four peaks are considered to be two peaks derived from a hexagonal crystal structure and two peaks derived from a rhombohedral crystal structure. In the case of artificial graphite, it is generally considered that only two peaks derived from a hexagonal crystal structure appear. In the X-ray diffraction pattern, the ratio of the peak intensity derived from the (012) plane to the peak intensity derived from the (100) plane ((012) / (100)) is preferably 0.3 or more, more preferably 0.4 or more. The peak intensity ratio ((012) / (100)) is preferably 0.6 or less. Here, the (100) plane originates from a hexagonal crystal structure, and the (012) plane originates from a rhombohedral crystal structure.

[0043] The average particle size of the solid natural graphite is, for example, preferably 1 μm or more and 100 μm or less, and more preferably 5 μm or more and 50 μm or less. By setting the average particle size of the solid natural graphite to be equal to or more than the above lower limit, the solid natural graphite becomes easy to manufacture or handle. By setting the average particle size of the solid natural graphite to be equal to or less than the above upper limit, the electronic conductivity of the negative electrode active material layer is improved.

[0044] The content of solid natural graphite in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, more preferably 90% by mass or more and 98% by mass or less, and even more preferably 95% by mass or more in some cases. By setting the content of solid natural graphite within the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer, and to further reduce the resistance increase rate after charge / discharge cycles.

[0045] The negative electrode active material may contain other negative electrode active materials other than solid natural graphite. Examples of other negative electrode active materials include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the carbon materials include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, graphite other than solid natural graphite, non-graphitic carbon (easily graphitized carbon or non-graphitized carbon), etc. However, the content of solid natural graphite in the total negative electrode active material is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 99 mass% or more, and particularly preferably 100 mass%. In this way, when the negative electrode active material is substantially composed of only solid natural graphite, the resistance increase rate after charge / discharge cycles tends to be further reduced.

[0046] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass or more and 99% by mass or less, more preferably 90% by mass or more and 98% by mass or less, and even more preferably 95% by mass or more in some cases. By setting the content of the negative electrode active material within the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer.

[0047] The negative electrode active material layer preferably contains CMC, which is one of the polysaccharide polymers exemplified as a thickener for the positive electrode. The negative electrode active material layer preferably contains a metal salt of CMC, more preferably contains an alkali metal salt of CMC, and even more preferably contains a sodium salt of CMC (sodium carboxymethylcellulose). In such a case, the resistance increase rate after charge-discharge cycles tends to be further reduced.

[0048] The content of the thickener such as CMC (including salt form) in the negative electrode active material layer is preferably 0.1% by mass to 5% by mass, more preferably 0.4% by mass to 3% by mass, and even more preferably 0.6% by mass to 2% by mass. By setting the content to the lower limit or more, the resistance increase rate after charge / discharge cycles is further reduced. On the other hand, by setting the content to the upper limit or less, the energy density of the negative electrode active material layer can be increased.

[0049] In some cases, it may be preferable that the negative electrode active material layer does not contain a conductive agent. In the secondary battery, the negative electrode active material layer contains solid natural graphite having good conductivity, and since at least a part of the electrode body is pressed in a discharged state, the conductivity between the particles of the solid natural graphite can be sufficiently ensured. Therefore, the secondary battery can exhibit good charge / discharge performance even if the negative electrode active material layer does not contain a conductive agent. In addition, when the negative electrode active material layer does not contain a conductive agent, the content of the negative electrode active material can be increased, and the energy density of the negative electrode active material layer can be increased.

[0050] The content of the binder in the negative electrode active material layer may be, for example, 0.1% by mass or more and 10% by mass or less, but is preferably 0.2% by mass or more and 4% by mass or less, more preferably 0.4% by mass or more and 2% by mass or less, and even more preferably 0.6% by mass or more and 1.5% by mass or less. By setting the content of the binder within the above range, the negative electrode active material can be stably held while increasing the energy density of the negative electrode active material layer. In addition, when sodium carboxymethylcellulose or the like is used as a thickener, even in such a case where the content of the binder is relatively small, the dispersibility of the binder is high, and the resistance increase rate after the charge and discharge cycle can be sufficiently reduced. As the binder in the negative electrode active material layer, the same materials as those exemplified for the positive electrode can be mentioned, but elastomers are preferable, and styrene butadiene rubber is more preferable.

[0051] The negative electrode can be produced, for example, by applying a negative electrode mixture paste directly or via an intermediate layer to a negative electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The negative electrode mixture paste contains each component constituting the negative electrode active material layer, including a negative electrode active material and optional components such as a conductive agent, a binder, and a thickener. The negative electrode mixture paste usually further contains a dispersion medium.

[0052] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of the liquid retention of the nonaqueous electrolyte. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0053] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.

[0054] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0055] (Non-aqueous electrolyte) The nonaqueous electrolyte secondary battery includes a nonaqueous electrolyte as an electrolyte solution. The nonaqueous electrolyte solution can be appropriately selected from known electrolyte solutions. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0056] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0057] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.

[0058] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0059] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0060] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0061] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0062] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0063] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, and propane sulfite. sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like. These additives may be used alone or in combination of two or more.

[0064] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0065] (Pressing against the electrode body) In the discharged state, the electrode body is in a state where at least a part of it is pressed. Usually, the electrode body is pressed in the direction in which the positive electrode, the negative electrode, and the separator are stacked (thickness direction of each layer). That is, the positive electrode active material layer and the negative electrode active material layer are pressed in the direction in which they are crushed in the thickness direction. However, a part of the electrode body (for example, a pair of curved surfaces in a flat wound electrode body) may not be pressed. In addition, only a part of the flat part of the laminated electrode body and the flat wound electrode body, for example, only the central part, may be pressed. In addition, since at least a part of the electrode body is pressed in the discharged state, the secondary battery maintains sufficient conductivity in the active material layer even when it is repeatedly charged and discharged, and the capacity retention rate after the charge and discharge cycle also tends to increase.

[0066] In order to make at least a part of the electrode body in a discharged state compressed, for example, it is preferable to use a rectangular container as the container, and to design the secondary battery so that the ratio (T1 / T2) of the thickness (T1) of the electrode body in a discharged state to the inner dimension (T2) of the rectangular container in the thickness direction of the electrode body exceeds 1.00. The thickness (T1) of the electrode body is the thickness of the stacked positive electrode, negative electrode, and separator in the thickness direction, and is the thickness of the electrode body in a dry state and in a state where it is not compressed. In this case, the electrode body is usually a flat wound electrode body or a laminated electrode body, and is preferably a flat wound electrode body. In addition, the inner dimension (T2) of the rectangular container is the inner dimension in a state where the electrode body is not inserted. The ratio (T1 / T2) is preferably 1.01 or more. In addition, the upper limit of the ratio (T1 / T2) may be, for example, 1.1 or 1.05, taking into consideration the ease of inserting the electrode body into the container.

[0067] In the secondary battery, apart from or in addition to setting the ratio (T1 / T2) to more than 1.00, the container may be configured to be pressed from the outside by a pressing member or the like. At this time, at least a part of the electrode body housed in the container is in a state of being pressed from the outside of the container, i.e., via the container. The pressing member may be a restraining member that restrains the shape of the container. The pressing member (restraining member) is provided so as to sandwich and press the electrode body from both sides in the thickness direction, for example, via the container. The pressed surface of the electrode body is in contact with the inner surface of the container directly or via another member. Therefore, the electrode body is pressed by pressing the container. Examples of the pressing member include a restraining band and a metal frame. For example, the metal frame may be configured so that the load can be adjusted by a bolt or the like. Also, a plurality of secondary batteries (electricity storage elements) may be arranged in the thickness direction of the electrode body, and fixed using a frame or the like in a state in which the plurality of secondary batteries are pressed from both ends in the thickness direction.

[0068] The electric storage element of this embodiment has a reduced resistance increase rate after charge / discharge cycles. In general electric storage elements, when charge / discharge is performed at a high current density (high rate), the resistance increase after charge / discharge cycles is usually significant. This is thought to be because the movement of the electrolyte cannot keep up with the high speed charge / discharge, and parts of the electrode body where the electrolyte is depleted are particularly likely to occur. For this reason, the electric storage element of this embodiment, which is configured to prevent the electrolyte from being depleted in the electrode body, is suitable for use in applications where charge / discharge is performed at a high current density, such as automotive power sources for electric vehicles (EVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), and the like.

[0069] The shape of the energy storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery.

[0070] FIG. 1 shows an energy storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51. In the energy storage element 1 of FIG. 1, a pressing member (not shown) or the like may be provided to pressurize the container 3 and the electrode body 2 housed in the container 3 by, for example, sandwiching both sides of the container 3 (usually the front side and the back side in FIG. 1).

[0071] <Configuration of the power storage device> The energy storage element of this embodiment can be mounted as an energy storage unit (battery module) configured by assembling a plurality of energy storage elements 1 in a power source for an automobile such as an EV, HEV, or PHEV, a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one energy storage element included in the energy storage unit.

[0072] 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects two or more energy storage elements 1, a bus bar (not shown) that electrically connects two or more energy storage units 20, and the like. The energy storage unit 20 or the energy storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more energy storage elements. The energy storage unit 20 or the energy storage device 30 may be provided with a pressure member (restraint member) such as a frame (not shown).

[0073] <Method of manufacturing the energy storage element> The method for producing the energy storage element of the present embodiment can be appropriately selected from known methods. The method for producing the energy storage element of the present embodiment includes, for example, preparing an electrode body, preparing an electrolyte, and housing the electrode body and the electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween.

[0074] The electrolyte solution can be contained in the container by any known method, for example, by injecting the electrolyte solution through an inlet formed in the container and then sealing the inlet.

[0075] <Other embodiments> The energy storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0076] In the above embodiment, the case where the storage element is used as a chargeable and dischargeable non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) has been described, but the type, shape, size, capacity, etc. of the storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. The storage element of the present invention can also be applied to storage elements in which the electrolyte is an electrolyte other than a non-aqueous electrolyte.

[0077] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The porosity of the graphite (solid natural graphite and hollow natural graphite) used in the following examples is a value measured by the method described above.

[0079] [Example 1] (Preparation of positive electrode) Positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture paste was prepared using O2, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, AB, and PVDF was 93:4:3 (solid content conversion). The positive electrode mixture paste was applied to both sides of aluminum foil as a positive electrode substrate and dried. Then, roll pressing was performed to obtain a positive electrode.

[0080] (Preparation of negative electrode) A negative electrode mixture paste was prepared by mixing solid natural graphite as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, carboxymethylcellulose ammonium (CMC-NH4) as the thickener, and water as the dispersion medium. The mass ratio of solid natural graphite, SBR, and CMC-NH4 was 98:1:1 (solid content conversion). The negative electrode mixture paste was applied to both sides of copper foil as the negative electrode substrate and dried. Then, a roll press was performed to obtain a negative electrode. The porosity of the solid natural graphite calculated by the above method was 0.49%.

[0081] (Non-aqueous electrolyte) A 1.2 mol / dm 3 LiPF6 was dissolved in the aqueous solution at a concentration of 100% to obtain a non-aqueous electrolyte solution.

[0082] (Separator) The separator used was a microporous polyolefin film.

[0083] (Battery Assembly) A wound electrode body was obtained using the positive electrode, negative electrode, and separator. The thickness of the electrode body was adjusted so that the ratio (T1 / T2) of the thickness of the electrode body in the discharged state after the initial charge and discharge to the inner dimension (T2) of the rectangular container in the thickness direction of the electrode body was 1.019. The electrode body was placed in a rectangular container, and a nonaqueous electrolyte was poured in and sealed. This resulted in the storage element (secondary battery) of Example 1.

[0084] [Example 2] An electricity storage element of Example 2 was obtained in the same manner as in Example 1, except that the thickener was changed to sodium carboxymethyl cellulose (CMC-Na).

[0085] [Comparative Example 1] Except for changing the negative electrode active material to hollow natural graphite, an electricity storage element of Comparative Example 1 was obtained in the same manner as in Example 1. The porosity of the hollow natural graphite calculated by the above-mentioned method was 7.59%.

[0086] [Reference example 1] Except for changing the negative electrode active material to hollow natural graphite and adjusting the thickness of the electrode body so that the ratio (T1 / T2) of the thickness of the electrode body in the discharged state after initial charge and discharge (T1) to the inner dimension (T2) of the rectangular container in the thickness direction of the electrode body was 0.996, the same procedure as in Example 1 was carried out to obtain an energy storage element of Reference Example 1. The porosity of the hollow natural graphite calculated by the above-mentioned method was 7.59%.

[0087] [evaluation] (Initial charge / discharge) Each of the obtained storage elements was charged at a constant current of 1C to 4.1V in a temperature environment of 25°C, and then charged at a constant voltage of 4.1V. The charging was terminated when the total charging time reached 3 hours. After a 10-minute pause, the elements were discharged at a constant current of 1C to 2.5V, and then another 10-minute pause was provided. These charging and discharging steps constitute one cycle, and two cycles were performed. (Rate of increase in resistance) Each of the obtained storage elements was charged at a constant current of 1.0 C at 25° C. to bring the SOC to 50%. After storing in a thermostatic chamber at −10° C. for 4 hours, the element was discharged at a current of 0.2 C, 0.5 C, or 1.0 C for 30 seconds. After each discharge, the element was charged at a constant current of 1.0 C to bring the SOC to 50%. The relationship between the current and the voltage 10 seconds after the start of discharge in each discharge was plotted, and the DC resistance (initial resistance) was calculated from the slope of the straight line obtained by plotting the three points. Next, the following charge-discharge cycle test was carried out. At 55° C., the battery was charged at a constant current of 8 C up to 4.1 V. Then, the battery was discharged at a constant current of 8 C up to 2.5 V. This charging and discharging was carried out for 500 hours. After the charge-discharge cycle test, the DC resistance (resistance after the charge-discharge cycle test) of each secondary battery was measured in the same manner as in the measurement of the initial resistance. The resistance increase rate after the charge-discharge cycle test was calculated by dividing the difference between the resistance after the charge-discharge cycle test and the initial resistance by the initial resistance. The results are shown in Table 1.

[0088] (Expansion rate of negative electrode active material layer) The same negative electrode mixture paste as that prepared in Examples 1 and 2, Comparative Example 1, and Reference Example 1 was applied to one side of a copper foil as a negative electrode substrate, and then dried and roll-pressed to prepare a negative electrode, and a test cell was prepared using metallic lithium as a counter electrode. The electrolyte was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:35:35, with 1.0 mol / dm 3 A non-aqueous electrolyte solution in which LiPF6 was dissolved at a concentration of The following charge-discharge cycle test was performed on each test cell. At 25°C, the cells were charged at a constant current of 1C to 0.02V, and then charged at a constant voltage of 0.02V. The charge was terminated when the current during the constant voltage charge decayed to 0.01C. A rest period of 10 minutes was then provided. Next, a constant current discharge was performed at a current of 1C to 2V, and a rest period of 10 minutes was then provided. These charge and discharge steps were repeated for 8 cycles. Note that the reduction reaction in which lithium ions are absorbed into the negative electrode active material is referred to as "charge", and the oxidation reaction in which lithium ions are released from the negative electrode active material is referred to as "discharge". The expansion coefficient of the negative electrode active material layer was calculated by dividing the difference in thickness between before and after the charge-discharge cycle test by the thickness of the negative electrode active material layer before the charge-discharge cycle test. The results are shown in Table 1.

[0089] [Table 1]

[0090] As shown by Reference Example 1 and Comparative Example 1, when hollow natural graphite is used as the negative electrode active material, the ratio (T1 / T2) of the thickness (T1) of the electrode body to the inner dimension (T2) of the rectangular container in the thickness direction of the electrode body exceeds 1.00, and when at least a part of the electrode body is pressed in the discharged state (Comparative Example 1), the resistance increase rate after the charge-discharge cycle becomes very large. In contrast, it is found that by using solid natural graphite as the negative electrode active material as in Examples 1 and 2, the resistance increase rate is greatly reduced, even though at least a part of the electrode body is pressed in the discharged state. Furthermore, it is found that when CMC-Na is used as the thickener as in Example 2, the resistance increase rate is further reduced.

[0091] [Reference Examples 2 to 6] The storage elements of Reference Examples 2 to 6 were obtained in the same manner as Comparative Example 1, except that the thickness of the electrode body was adjusted so that the ratio (T1 / T2) of the thickness of the electrode body in a discharged state (T1) to the inner dimension (T2) of the rectangular container in the thickness direction of the electrode body was 0.970, 0.983, 1.014, 1.037, and 1.060, respectively.

[0092] (Capacity maintenance rate) The following charge-discharge cycle test was performed on each of the energy storage elements of Reference Examples 2 to 6. At 55° C., the elements were charged at a constant current of 8 C to 4.1 V. Then, the elements were discharged at a constant current of 8 C to 2.5 V. This charging and discharging was performed for 250 hours. FIG. 3 shows the retention rate of the discharge capacity after 250 hours of charge-discharge cycles relative to the discharge capacity at the first cycle for each of the energy storage elements of Reference Examples 2 to 6.

[0093] As shown in FIG. 3, when the ratio (T1 / T2) exceeds 1.00 and at least a portion of the electrode body is pressed in a discharged state, the decrease in discharge capacity due to charge / discharge cycles is suppressed, and the capacity retention rate is high. [Industrial Applicability]

[0094] The present invention can be applied to electronic devices such as personal computers and communication terminals, and to energy storage elements used as power sources for automobiles and the like. [Explanation of symbols]

[0095] 1 Energy storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. The battery includes an electrode assembly having a negative electrode containing a negative electrode active material, an electrolyte, and a rectangular container for accommodating the electrode assembly and the electrolyte, At least a portion of the electrode body is pressed in a discharge state, the electrode body is sandwiched and pressed by opposing inner surfaces of the rectangular container in a thickness direction of the negative electrode, where T1 is a thickness of a portion of the electrode body pressed by the opposing inner surfaces in a discharged state in a dry and unpressed state, and T2 is an inner dimension which is a distance between the opposing inner surfaces of the rectangular container in a state in which the electrode body is not contained therein, a ratio T1 / T2 of the thickness to the inner dimension of the rectangular container is 1.01 or more, the negative electrode active material comprises solid natural graphite particles, An energy storage element in which the area ratio of voids within a particle to the entire area of ​​the particle, as observed in a cross section of the solid natural graphite particle in an SEM image obtained using a scanning electron microscope (SEM), is 2% or less.

2. 2. The energy storage element according to claim 1, wherein the content of the solid natural graphite particles in the negative electrode active material is 99 mass % or more.

3. The energy storage element according to claim 1 or 2, wherein the negative electrode further contains sodium carboxymethylcellulose.

Citation Information

Patent Citations

  • Negative pole material for lithium battery, and lithium battery

    JP2005222933A

  • Negative electrode for power storage device, and power storage device

    JP2017069039A

  • Secondary battery exterior body and secondary battery

    JP2019139872A

  • Negative electrode material for non-aqueous secondary battery, negative electrode for non-aqueous secondary battery, and non-aqueous secondary battery

    JP2019175775A

  • Electricity storage element and method for producing electricity storage element

    WO2020054708A1